THYROID PROFILE ABNORMALITIES IN LIVER CIRRHOSIS: CORRELATION WITH CHILD-PUGH CLASS AND ETIOLOGICAL SUBTYPES (Asian Journal of Medical Research and Health Sciences, 2026)
Aim:  This study aimed to evaluate the thyroid profile in patients with liver cirrhosis and to correlate the findings with the severity and etiology of the underlying liver disease. Methods: This cross-sectional, observational study was conducted on 74 patients diagnosed with liver cirrhosis. Serum levels of Triiodothyronine (T3), Thyroxine (T4), and Thyroid Stimulating Hormone (TSH) were estimated. The severity of liver disease was assessed using the Child-Pugh score. Patients were categorized by etiology (alcoholic, viral, and cryptogenic/other). Statistical analysis was performed using ANOVA and Pearson's correlation coefficient to determine associations. Results: The study population (n=74) had a mean age of 54.2 ± 9.8 years. A significant decline in mean T3 levels was observed with increasing severity of cirrhosis (Child-Pugh A: 1.12 ng/mL, B: 0.73 ng/mL, C: 0.45 ng/mL; p